Structural Behaviour and Fatigue Life Assessment of Eco-Efficient Two-Layer Concrete Pavements Incorporating Recycled Asphalt Aggregates (Scientific Journal of Research Studies in Future Civil Engineering, 2025)
Two-layer concrete pavements have emerged as a strategic solution for enhancing structural efficiency, reducing material consumption, and improving long-term sustainability in rigid pavement systems. The integration of recycled asphalt aggregates within the top or bottom concrete layers introduces additional benefits related to resource conservation and waste valorisation, while simultaneously influencing mechanical performance and fatigue resistance. This study investigates the structural behaviour and fatigue life of eco-efficient two-layer concrete pavements containing recycled asphalt aggregates, drawing on recent advancements in composite pavement engineering and validated datasets reported in prior experimental and field studies. The research examines flexural response, interlayer bonding, damage propagation, and stiffness evolution under repeated loading representative of urban traffic conditions. Emphasis is placed on understanding how recycled asphalt content, aggregate morphology, binder characteristics, and layer configuration jointly influence performance indicators such as flexural strength, stiffness modulus, crack initiation thresholds, and cumulative fatigue damage. A comprehensive analytical framework is developed to assess fatigue life using established mechanistic–empirical models while incorporating real loading spectra and temperature variations. Experimental results available in prior literature demonstrate that moderate proportions of recycled asphalt aggregates can improve energy absorption capacity and delay crack onset, though excessive content may weaken interfacial integrity. The findings highlight the significance of optimized mixture design, proper gradation control, and enhanced bonding treatments to achieve structural reliability over the service life. The study ultimately contributes to a deeper understanding of sustainable pavement engineering by demonstrating how recycled asphalt materials can be safely and effectively integrated into two-layer concrete systems without compromising performance. These insights support broader implementation of eco-efficient pavement technologies that align with circular-economy principles and contemporary infrastructure sustainability goals.